(untitled) (Journal of Eye Movement Research, 2014)
Latest developments in remote and head-mounted eye tracking and automated eye movement analysis point the way toward unobtrusive eye-based human-computer interfaces that will become pervasively usable in everyday life. We call this new paradigm pervasive eye tracking – continuous eye monitoring and analysis 24/7. Pervasive Eye Tracking and Mobile Eye-Based Interaction (PETMEI) is a workshop series that revolves around the theme of pervasive eye-tracking as a trailblazer for pervasive eye-based human-computer interaction and eye-based context-awareness. This special issue is composed from extended versions of the top-scoring papers from the 3rd workshop in the PETMEI series held in 2013.